EKSPLORASI KEARIFAN LOKAL DALAM PEMBELAJARAN GEOMETRI: MENINGKATKAN KETERAMPILAN SPASIAL DENGAN GEOBOARD - Rahmadani, Elfira; Syafitri, Ely; Nisa, Khairun; Andini, Putri; Putri, Gladis Syaharani (Jurnal Pemberdayaan Sosial dan Teknologi Masyarakat, 2025)
This community service research aims to improve the spatial skills of elementary school students through local wisdom-based geometry learning with geoboard media. The main problem faced is the low understanding of students towards geometry concepts due to the abstract and less contextual learning approach. The method used is Participatory Action Research (PAR) which actively involves teachers and students in planning, implementation, and evaluation. The activity was carried out at UPTD SDN 014686 Sidomulyo, with the participation of 90 grade III students. The results showed a significant increase in students' spatial skills: 88% of students found it easier to understand geometric shapes, 91% showed active involvement, and 94% hoped that this method would continue to be used. In addition, 100% of teachers stated that this method was effective and increased their confidence in teaching. The use of geoboards and the integration of local cultural motifs have been proven to create contextual, enjoyable, and meaningful learning experiences. The conclusion of this activity is that local wisdom-based geometry learning with the help of geoboards is effective in improving students' spatial skills and is relevant to be applied widely